Perancangan Busana Uniseks Bergaya Co-Ed Androgynous Berbasis Konsep Sustainable Fashion - Dewa Made Weda Githapradana; Rahayu Budhi Handayani; Gabriela Laras Dewi Swastika (JURNAL RUPA, 2022)
Covid-19 pandemic resulted many changes and adjustments in various sectors of life, including the creative fashion industry sector. One of the topics that came out was the concept of sustainable fashion as a solution to overcome the challenges of changing times. One of the ideas for implementing the concept is “reduce-reuse-recycle”. The topic of this research is the application of the reduce-reuse-recycle concept in the design of co-ed androgynous unisex fashion using clothing waste, unsold clothing stock, and leftover fabric scraps. The topic of unisex clothing is a global fashion trend phenomenon that represents the efficiency of product differentiation as well as a gender identity campaign through appearance. The research problem is to find a suitable concept of design development for a unisex fashion product with co-ed androgynous style based on sustainable. The purpose of the research is to determine the concept and process of designing a unisex fashion product with a co-ed androgynous style based on a sustainable concept. The research method uses descriptive qualitative methods through triangulation (combined) data collection techniques covering several ways, namely literature, observation, interviews, and experimental. The design method uses the DUCMOT fashion system design stage with the design process in research and experimental testing. This concept not only has a positive impact on the surrounding environment but can also hone the creativity of industry players in utilizing and extending the life cycle of a product into new, innovative products. KeywordsCo-ed Androgynous, Gender Fluid, Sustainable Fashion, Unisex, Upcycle Design